2016
DOI: 10.3389/fphar.2016.00348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine on Resting-State EEG Activity and Their Relationship to Perceptual/Dissociative Symptoms in Healthy Humans

Abstract: N-methyl-D-aspartate (NMDA) receptor antagonists administered to healthy humans results in schizophrenia-like symptoms, which preclinical research suggests are due to glutamatergically altered brain oscillations. Here, we examined resting-state electroencephalographic activity in 21 healthy volunteers assessed in a placebocontrolled, double-blind, randomized study involving administration of either a saline infusion or a sub-anesthetic dose of ketamine, an NMDA receptor antagonist. Frequency-specific current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 140 publications
11
73
1
Order By: Relevance
“…Consistent in both animal and human studies, however, is the observation that ketamine increases activity of brain waves in the gamma (30 to 60 Hz) range. De la Salle et al reported such an increase in gamma current density in the default mode network implicated in schizophrenia, as well as activation of gamma frequencies across the cerebrum [12]. This finding supports a disinhibition model of HPPD.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent in both animal and human studies, however, is the observation that ketamine increases activity of brain waves in the gamma (30 to 60 Hz) range. De la Salle et al reported such an increase in gamma current density in the default mode network implicated in schizophrenia, as well as activation of gamma frequencies across the cerebrum [12]. This finding supports a disinhibition model of HPPD.…”
Section: Discussionsupporting
confidence: 77%
“…This is evidenced by the effect of NMDA receptor blockade on alpha activity in humans. 67 The hypofunction of the NMDA receptors in SCZ is known as cortical hyper-excitation by disinhibitory pyramidal neurons. 68 Improved cognitive performance is indexed by increased upper alpha power (individual alpha frequency, 8-10 Hz [AE2 Hz]) at the pre-stimulus interval in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies add to the confusion by demonstrating that some patients demonstrate increased gamma oscillations and associated connectivity [1416]. In addition, measurement of gamma rhythms in patients with specific polymorphisms associated with schizophrenia revealed that most correlated with elevated, rather than reduced, gamma power [17].…”
Section: Diverse Changes In Gamma Rhythm Generation Associated With Smentioning
confidence: 99%
“…However, the literature is again equivocal. Decreases in delta rhythm power and coherence have been reported [14,32,33] almost as frequently as elevations [3436]. Observations of wake-state theta activity are similarly mixed.…”
Section: Changes In Theta and Delta Rhythms In Schizophreniamentioning
confidence: 99%